Biomagnification and trophic transfer of total mercury and methylmercury in a sub-tropical montane forest food web, southwest China. (August 2021) - Li, Chan; Xu, Zhidong; Luo, Kang; Chen, Zhuo; Xu, Xiaohang; Xu, Chengxiang; Qiu, Guangle
Abstract: Little is known about the bioaccumulation and trophic transfer of total mercury (THg) and methylmercury (MeHg) via food webs in terrestrial ecosystems, especially in subtropical forest ecosystems. In the present study, THg and MeHg were determined as well as the carbon (δ 13 C) and nitrogen (δ 15 N) isotope composition in samples of soils, plants, invertebrates, and songbird feathers to construct food webs in a remote subtropical montane forest in Mt. Ailao, southwest China and assess the bioaccumulation, biomagnification, and trophic transfer of Hg. Results showed that the trophic levels (TLs) of all consumers ranged from 0.8 to 3.3 and followed the order of songbirds > spiders > omnivorous insects > herbivorous insects > plants, and THg and MeHg exhibited a clear biomagnification up the food chain from plants-herbivorous/omnivorous insects-spiders-songbirds. The lowest MeHg concentration was observed in pine needles ranged from 0.104 to 0.949 ng g −1 with only a 1.6% ratio of MeHg to THg (MeHg%), while the highest MeHg concentrations ranged from 425 to 5272 ng g −1 in songbirds with MeHg% values of up to 96%. High values of trophic magnification slope (TMS) for THg (0.22) and MeHg (0.38) were observed in plant-invertebrate-songbird food chain, verifying the significant bioaccumulation of Hg, particularly MeHg, in the remote subtropical forest ecosystem. This study confirmed the production and efficient biomagnification of MeHg in remote subtropical montane forest and the significant bioaccumulation of MeHg in terrestrial top predators. Graphical abstract: Image 1 Highlights: THg and MeHg increased with trophic positions in forest food webs. THg exceeded adverse effect thresholds in insectivorous songbirds. MeHg significantly biomagnified in subtropical forest food webs. Abstract : Significant biomagnification of methylmercury exists in a remote subtropical forest food web.